2021
DOI: 10.1111/fog.12539
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on habitat models for adult bigeye tuna in the Indian Ocean based on gridded tuna longline fishery data

Abstract: Using the gridded fishery data to estimate the habitat preferences of bigeye tuna (Thunnus obesus) in the Indian Ocean is challenging, as it is still not clear what type of model is appropriate to make reliable habitat predictions. In this study, we tested two classes of habitat models: Generalized Additive Models (including Gaussian distribution GAM, Poisson distribution GAM, Negative Binomial distribution GAM, Tweedie class distribution GAM, and Zero‐inflated distribution GAM) and Maximum Entropy Model (MaxE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Studies incorporating environmental information consistently stress the importance of oxygen concentration and water column thermal structure in determining habitat extent in large pelagics (e.g. Arrizabalaga et al, 2015; Lehodey et al, 2008; Sharp, 1995; Zhang et al, 2021; Zhou et al, 2020). Like in most stock assessments (Skern‐Mauritzen et al, 2016), however, management advice mainly relies on the assessment of current status of the stock in relation to reference points, only exploiting short term memory emerging from changes in size structure at age (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies incorporating environmental information consistently stress the importance of oxygen concentration and water column thermal structure in determining habitat extent in large pelagics (e.g. Arrizabalaga et al, 2015; Lehodey et al, 2008; Sharp, 1995; Zhang et al, 2021; Zhou et al, 2020). Like in most stock assessments (Skern‐Mauritzen et al, 2016), however, management advice mainly relies on the assessment of current status of the stock in relation to reference points, only exploiting short term memory emerging from changes in size structure at age (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tagging studies have shown that BET inhabit the 0–100 m depth range at night and spend time in both 0–50‐m and 300–500‐m depth ranges during the day (Dagorn et al, 2000; Evans et al, 2008; Howell et al, 2010). Water column structure and thermocline depth [mixed layer depth (MLD)] were found to be important predictors of BET catch rates in the Indian Ocean (Zhang et al, 2021). The vertical distribution of South Pacific albacore tuna is constrained by thermal preferences and the vertical distribution of prey species but varies significantly by size and latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the response for the effort density model was the number of estimated angler-hours directed at black bass, with the natural logarithm of mean quarterly surface area applied as an offset (i.e., effort per hectare [EPH]). Offsets in each model were log transformed to account for the log link function within each GAM (Wood 2006), as is traditionally applied when using an offset within GAMs (e.g., Dance and Rooker 2019;Smith et al 2021;Zhang et al 2021).…”
Section: Generalized Additive Modelingmentioning
confidence: 99%